Revealing the nanometric structural changes in myocardial infarction models by time-lapse intravital imaging - Kuo, Chiung Wen; Pratiwi, Feby Wijaya; Liu, Yen-Ting; Chueh, Di-Yen; Chen, Peilin (Frontiers in Bioengineering and Biotechnology, 2022)
In the development of bioinspired nanomaterials for therapeutic applications, it is very important to validate the design of nanomaterials in the disease models. Therefore, it is desirable to visualize the change of the cells in the diseased site at the nanoscale. Heart diseases often start with structural, morphological, and functional alterations of cardiomyocyte components at the subcellular level. Here, we developed straightforward technique for long-term real-time intravital imaging of contracting hearts without the need of cardiac pacing and complex post processing images to understand the subcellular structural and dynamic changes in the myocardial infarction model. A two-photon microscope synchronized with electrocardiogram signals was used for long-term in vivo imaging of a contracting heart with subcellular resolution. We found that the structural and dynamic behaviors of organelles in cardiomyocytes closely correlated with heart function. In the myocardial infarction model, sarcomere shortening decreased from ~15% (healthy) to ~8% (diseased) as a result of impaired cardiac function, whereas the distances between sarcomeres increased by 100 nm (from 2.11 m to 2.21 m) in the diastolic state. In addition, T-tubule system regularity analysis revealed that T-tubule structures that were initially highly organized underwent significant remodeling. Morphological remodeling and changes in dynamic activity at the subcellular level are essential to maintain heart function after infarction in a heart disease model.